A Corpus Analysis of Gender Harassment Policies: Understanding Inclusivity and Cultural Dynamics in Pakistan - Dania Younas; Adnan Tahir (Corporum)
In evaluating the 2010 Anti-Harassment Law of Pakistan, the study combines an analysis of the discourse and the linguistic corpora related to the subject matter. This research utilizes corpus tools like AntConc (4.2.4) and Sketch Engine to examine gender framing, cultural sensitivity, trends, and patterns within legal discourses. This sheds light on van Dijk's writings on Language and Power (2008), which suggest that legal language constructs and solidifies unjust power relations. The lack of a modus operandi for addressing the gaps in ethnicity and transgender intersectionality indicates that state protection is heavily centralized. A limited emphasis on preventing harassment does not disguise the exclusionary inclusiveness of these measures. These findings help deepen the understanding of the sociocultural components embedded in Pakistan's legal framework and highlight the importance of gender equity legislative measures. Additionally, this research discusses the implications of discourse on legal inclusivity and emphasizes advocating for policy reforms that effectively address cultural and gender diversity in Pakistan.